1998
DOI: 10.1136/gut.42.6.799
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fibre and intestinal microflora: effects on intestinal morphometry and crypt branching

Abstract: Background-Fermentable dietary fibre has many eVects on the gastrointestinal tract. One is to alter epithelial crypt cell proliferation, especially in the colon. A discrepancy between epithelial cell production rates and intestinal weights has been noted previously: crypt cell production rates only increase if bacterial fermentation occurs, but intestinal wet weight can increase in the same animals without bacterial fermentation of fibre. Aims-To quantify intestinal cell populations in order to resolve the abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
61
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 31 publications
6
61
1
Order By: Relevance
“…Also in our experiment the considerable decrease of ileal protein digestibility at the lower P supplement was accompanied by an only minor increase of digesta viscosity and, in contrast, the high digesta viscosity induced by the greater amount of P was accompanied by a relatively small decrease of digestibility. This discrepancy between the effects of P on viscosity and ileal digestibility seems to confirm the assumption that the negative effect of P on ileal digestibility is also related to other factors, such as increased endogenous nitrogen losses and microbial fermentation in the gut (Schulze et al, 1995;McCullough et al, 1998) as well as digesta passage rate (Bartelt et al, 2002), which contribute to changes in the digestibility of nutrients, their absorption, and utilization.…”
Section: Discussionmentioning
confidence: 56%
“…Also in our experiment the considerable decrease of ileal protein digestibility at the lower P supplement was accompanied by an only minor increase of digesta viscosity and, in contrast, the high digesta viscosity induced by the greater amount of P was accompanied by a relatively small decrease of digestibility. This discrepancy between the effects of P on viscosity and ileal digestibility seems to confirm the assumption that the negative effect of P on ileal digestibility is also related to other factors, such as increased endogenous nitrogen losses and microbial fermentation in the gut (Schulze et al, 1995;McCullough et al, 1998) as well as digesta passage rate (Bartelt et al, 2002), which contribute to changes in the digestibility of nutrients, their absorption, and utilization.…”
Section: Discussionmentioning
confidence: 56%
“…However, in contrast to our hypothesis that an increase in the number of ileum goblet cells by DF ingestion might be associated with such a luminal bacterium component as endotoxin, the DF effect was unaffected by the antibiotic treatment in the rat ileum, even with a low endotoxin concentration. Only one study is currently available to indirectly support the present findings, McCullough et al 13) showing that an elemental diet containing 30% fiber (a 1:9 mixture of psyllium and wheat bran) increased the number of goblet cells in the small intestine of germ-free rats. Although they did not refer to the rat growth and food intake in their study, it is obvious that rats fed the 30% fiber diet could not meet the calorie requirement for normal growth by compensatory eating of the diet.…”
supporting
confidence: 58%
“…Nonetheless, it is conceivable that whole-organ hypertrophy could be related to changes in the number of smaller or larger cells, with little change in dry mass; histological studies are needed to clarify the cellular basis for the organ-mass changes we observed. More important, it is uncertain how feed particle size may be involved with the hindgut hypertrophy, but SCFAs are known to affect whole-organ trophic responses of the gut in other species (Goodlad et al 1989;Sakata 1995;McCullough et al 1998). For example, SCFAs are associated with hyperplasic stimulation of cell proliferation (Goodlad et al 1989), but they can also increase total cell counts in the gut by inhibiting apoptosis (Mentschel et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Such a mechanism would represent a direct effect of the physicochemical features of the ingesta, but there may also be indirect factors at play. For example, higher loads of fine particles increase digesta viscosity (Lentle et al 2004(Lentle et al , 2005, which, along with some SCFAs, stimulates mucus production (McCullough et al 1998;Shimotoyodome et al 2000;Piel et al 2005). Mucus aids the flow of digesta through the small intestine and colon, but it would also present the hindgut with a source of readily fermentable sugars (e.g., the glycoprotein coat), the main fermentative by-product of which is n-butyrate (Stevens and Hume 1995).…”
Section: Discussionmentioning
confidence: 99%